TREATMENT OF ONION SEEDS WITH PROPOLIS EXTRACT AND Plectranthus amboinicus IN THE CONTROL OF Aspergillus sp. - Carvalho, B. L.; Souza, E. P.; Anjos, L. V. S.; Nakada-Freitas, P. G.; Cardoso, A. I. I.; Amador, T. S.; Santos, T. P.; Magalhães, T. H. (Revista Brasileira de Engenharia de Biossistemas, 2019)
With a great concern for health and a preservation of the environment, the search for alternative sources of disease control and growth in agriculture. This is because agrochemicals are being used indiscriminately, putting human health and the environment at risk. As recent research shows which have efficient bioactive substances in the control of pathogens. For this reason, the objective of this work was to evaluate the effect of propolis extract and Plecthanthus amboinicus without treatment of onion seeds inoculated with Aspergillusflavus. As onion seeds were inoculated with the fungus Aspergillus sp. Subsequently, the treatments were applied with agitation of five minutes in solutions of propolis and P. amboinicus in the concentrations: 0; 5; 15; 25%. The experiment was set up in a 2 x 4 factorial scheme in a completely randomized design with five replicates. And for the solutions of P. amboinicus, culture media were prepared with BDA (potato-dextrose-agar) and 5 mm discs were inserted into the fungus, so that there was no evidence of in vitro development of the pathogen. As evaluated characteristics were: halo diameter of fungus growth (in vitro test); sanity test; first germination count; germination; dry mass of seedlings; root overhead length; length and emergency test. Peppermint and propolis extracts were not efficient in the control of the Aspergillus sp. fungus, by means of study concentrations. P. amboinicus extract used to treat onion seeds may have caused phytotoxicity, triggering lower values for most of the physiological quality characteristics of these seeds compared to the propolis extract.